Efektivitas Variasi Garam Salmiak (NH4Cl) Dan Sentrifugasi Pada Pemeriksaan Basil Tahan Asam Penderita Tuberculosis - Siregar, Saadah; Supriatin, Yati; Noor, Lanny (POLTEKKES KEMENKES YOGYAKARTA, 2017)
According to a report by WHO Indonesia, it is a case number three infected with tuberculosis. Tuberculosis disease is caused by Mycobacterium tuberculosis that belongs to acid-fast bacilli bacteria (BTA). Sputum smear examination microscopically still has many deficiencies caused by mucoprotein in sputum so that BTA cannot be separated from sputum, this is causing a false negative in reading result Microscope. The objective of this research is to know the most effective variation of concentration, speed and time of centrifugation on smear examination in tuberculosis patients. The research method used is experimental method and Design of complete Random Block design. Data were analyzed by statistic test with ANOVA test on SPSS. The result of the research is that at concentration 2% NH4Cl It can increase the number of BTA with optimal centrifugation speed / effective at 5000 rpm for 15 minutes. Suggestion for further research is to use salmaniac salt concentration with a concentration lower than 2%.